Synthesis of Metal-Organic Frameworks and Comparative Study of CO2 and SO2 Adsorption Properties - Hu, Yu-Ping; Tan, Chun-Ping; Wang, Shuang-Fei; Meng, Xiao-Bo (Asian Journal of Chemistry, 2012)
In this work, porous aluminum-trimesate (MIL-96), one of the metal-organic frameworks, has been synthesized at 210 ºC for 24 h. The MIL-96 adsorbs nitrogen readily at liquid nitrogen temperature to show permanent porosity (SBET = 507 m2/g, SLangmuir = 668 m2/g). The thermogravimetric analysis shows that the material is stable up to 350 ºC. CO2 and SO2 are adsorbed over the synthesized MIL-96 in the pressure of 0-50 bar at 40 ºC. The experimental results show that CO2 saturated adsorption amount on MIL-96 at 40 ºC is up to 5-25 mmol/g, is far superior to SO2 on the same conditions. Adsorption experimental results of SO2 on MIL-96 at various temperatures show that the adsorption capacity increases with temperature increases. Very interestingly, the saturated adsorption amount at 100 ºC is less than the one at 80 ºC, which may be explained that water vapour molecules hinder SO2 adsorption.